Design for Sustainability – Learning from Traditional Indian Products and Practices - Sejal Changede; Lisa Thomas; Stuart Walker (ITB Journal Publisher, LPPM ITB, 2022)
Mainstream design approaches for developing more sustainable ways of living are often underpinned by the very modern values that have been instrumental in creating our unsustainable world. These values include those of consumerism, economic growth, efficiency, and technological optimism – exemplified by mainstream Triple Bottom Line approaches, including the popular Circular Economy concept. Mounting evidence of unsustainability, however, suggests that such approaches may not be sufficient to bring about the scale of change required. We present initial findings from an ongoing research project that examines what Design for Sustainability can learn from traditional products and practices in India that are not underpinned by modern values. We focused on one traditional product, the mortar and pestle, comparing it with a contemporary spice grinder. We offer five initial findings for developing contemporary products in a more comprehensive and holistic manner than is currently the case.